From the Geography of Innovation to Development Policy Analysis: The GMR-approach - Varga, Attila (PTE KTK Műhelytanulmányok, 2022)
Knowledge based local economic development policies (often labeled also as “cluster development” or policies designed to distribute Structural Funds over the EU territory within the framework of “national development plans”) are implemented with an explicit or implicit aim towards broader state, national or even supra national interests. The main issues are growth (at the supra regional level) and convergence (across regions). How different mixtures of the instruments of local development policies can help approach theses aims – or more precisely to what extent these policies may serve either of the targets or perhaps both of them? The related theoretical and empirical literature in the new economic geography, economic growth and the geography of innovation fields is extensive. However economic models drawing from this literature and constructed for the aim of evaluating actual development policy decisions in the light of the growth and convergence targets are rare. This paper serves two aims. First it explains a manner how the geography of innovation literature can contribute to develop a sub-model that can be used for assessing the static impacts of development policy interventions in the GMR-Hungary model. Second to demonstrate the power of such a model that incorporates the lessons from the geography of innovation literature policy simulation results with GMR at the regional, interregional and macro levels are provided.